Discussion of the changed of Su Shi’s Words (Ci) Creation in Life and Environment and The Process of Words (Ci) Written by Using Poetry: 论苏轼填词的生活场合演变与其词诗化之过程 - TEY, Shi Bin (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2016)
Life is often an occasion of human creative materials. Su Shi’s words (Ci) written by using poetry have its process. This process has the close relationship with Su Shi’s life and environment. Since Su Shi enter the capital to take imperial examination and during he as a government official, his responsibility for supplying the military’s equipments and materials is very important, he don’t has the environment and time to practice his words. Until he becomes the local magistrate in Hangzhou, the situation has changed. During Hangzhou period, he was influenced by Zhang Xian and others senior. He put personal experience in daily life, emotions, ideals, and the history of ancient in his written of words; to express lonely and no sustenance; upgrade the level of philosophy and make the words (Ci) wisely and vigorous. This is reflected in the creation of Su Shi after he relegated to Huangzhou. Therefore, this paper argues that Su Shu’s written from words (Ci) to poetry began in his Hangzhou period; While he become governor of Mizhou and Xuzhou period, his written from words (Ci) to poetry is getting maturity and peak during his living in Huangzhou. Keywords: Su Shi, life and environment; The Process of Words (Ci) Written by Using Poetry.